Impact of Drug Size on Brain Tumor and Brain Parenchyma Delivery after a Blood–Brain Barrier Disruption. Issue 5 (May 2014) - Blanchette, Marie; Tremblay, Luc; Lepage, Martin; Fortin, David
Drug delivery to the brain is influenced by the blood–brain barrier (BBB) and blood–tumor barrier (BTB) to an extent that is still debated in neuro-oncology. In this paper, we studied the delivery across the BTB and the BBB of compounds with different molecular sizes in normal and glioma-bearing rats. Studies were performed at baseline as well as after an osmotic BBB disruption (BBBD) using dynamic contrast-enhanced magnetic resonance imaging and two T1, contrast agents (CAs), Magnevist (743 Da) and Gadomer (17, 000 Da). More specifically, we determined the time window for the BBB permeability, the distribution and we calculated the brain exposure to the CAs. A different pattern of accumulation and distribution at baseline as well as after a BBBD procedure was observed for both agents, which is consistent with their different molecular size and weight. Baseline tumor exposure was threefold higher for Magnevist compared with Gadomer, whereas postBBBD tumor exposure was twofold higher for Magnevist. Our study clearly showed that the time window and the extent of delivery across the intact, as well as permeabilized BTB and BBB are influenced by drug size.